Sex Differences in the Association Between Internalizing Symptoms and Craving in Methamphetamine Users. Issue 6 (November 2016) - Hartwell, Emily E.; Moallem, Nathasha R.; Courtney, Kelly E.; Glasner-Edwards, Suzette; Ray, Lara A.
Abstract : Objectives: Methamphetamine (MA) users often have substantial psychiatric comorbidities, with nearly a third reporting lifetime mood disorders and over a quarter reporting lifetime anxiety disorders. Female MA users are more likely to endorse depression and anxiety symptoms compared with men. Craving has been related to mood/anxiety symptoms in MA users. To extend the literature on sex differences in MA use disorder, the present study examines the role of sex as a moderator of the relationship between mood/anxiety symptoms and MA craving. Methods: Participants (N = 203) were nontreatment-seeking, current MA users, recruited from the Los Angeles community for enrollment in a larger pharmacotherapy trial. At the assessment visit, participants completed multiple measures including the Methamphetamine Urge Questionnaire, the Beck Depression Inventory, and the Beck Anxiety Inventory. Results: The relationship between depression symptomatology and MA craving was moderated by sex ( F = 6.18, P = 0.01), such that the relationship was positive and significant for men ( P < 0.001), but was not significant for women. Similarly, sex significantly moderated the relationship between anxiety and MA craving ( F = 5.99, P = 0.02), such that the relationship was also positive and significant in men, but not in women ( P < 0.001). Conclusions: These results suggest that men may be more sensitive to the effects of internalizing symptoms on MA craving than women. Given craving's propensity to predict relapse, these initial findings indicate the necessity of treating comorbid psychiatric problems in male MA users, which may in turn assist in the attenuation of craving.